2019
DOI: 10.1186/s12870-019-1863-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of poplar NF-YB gene family and identified PtNF-YB1 important in regulate flowering timing in transgenic plants

Abstract: Background: Compared with annual herbaceous plants, woody perennials require a longer period of juvenile phase to flowering, and many traits can be only expressed in adulthood, which seriously makes the breeding efficiency of new varieties slower. For the study of poplar early flowering, the main focus is on the study Arabidopsis homologue gene CO/FT. Based on studies of Arabidopsis, rice and other plant species, some important research progress has been made on the regulation of flowering time by NF-Y subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…They may be involved in the flowering process of tobacco and need further study. In addition, ZmNF-YC2 and PtNF-YB1 have also been identified to play a role in flowering regulation in maize and poplar 41 , 42 . Studies have shown that OsNF-YB2/B3/B4 affects chloroplast biosynthesis 43 , and the orthologous gene NtNF-YB30 of OsNF-YB3 may be a candidate gene involved in chloroplast synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They may be involved in the flowering process of tobacco and need further study. In addition, ZmNF-YC2 and PtNF-YB1 have also been identified to play a role in flowering regulation in maize and poplar 41 , 42 . Studies have shown that OsNF-YB2/B3/B4 affects chloroplast biosynthesis 43 , and the orthologous gene NtNF-YB30 of OsNF-YB3 may be a candidate gene involved in chloroplast synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that NF-Y is involved in regulating the flowering of plants, such as AtNFY-B2/B3/C2/C3/C4/C9 [ 44 , 45 ], PtNF-YB1 [ 46 ], and ZmNF-YA3/C2 [ 47 ]. Intriguingly, most of the genes were highly expressed in melon female and male flowers, or reached the peak value, such as CmNF-YA4/A5 , CmNF-YB4/B5/B6/B10, and CmNF-YC1/C2/C3/C7/C8 ( Figure 7 a), implying that these genes might regulate the flowering of melon.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with annual plants, most woody plants need a longer juvenile period before entering the flowering period, and many traits can only be expressed after reaching maturity. However, economic forests and timber forests have the problems of long a juvenile period and late flowering, which seriously limit the improvement of their economic benefits and production development, as well as their breeding process [ 2 , 3 , 4 ]. Therefore, promoting early flowering, shortening the juvenile period, and accelerating the breeding cycle of trees are of great significance to the development of forestry science and the study of the molecular mechanisms of plant sexual reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the poplar NF-Y gene in flowering. In recent years, studies have shown that overexpression of poplar PtNF-YB2 in Arabidopsis and tomato can induce earlier flowering [ 3 ], and overexpression of PtNF-YA9 can delay flowering in Arabidopsis [ 29 ]. However, research on the flowering of poplar NF-YC is lacking.…”
Section: Introductionmentioning
confidence: 99%